Financial strain, financial management practices, marital satisfaction and marital stability among newlyweds - Suardi Sawai Canon, Joki Perdani Sawai; Juhari, Rumaya; Kahar, Rojanah; Ismail, Zanariah; Sawai, Rezki Perdani (Accounting Research Institute (ARI), Universiti Teknologi MARA, 2018)
Money does matter especially in the family life and it affects marital satisfaction and marital stability. The purposes of this study are to examine the relationship between financial strain and financial management practices, and marital satisfaction and marital stability. 278 married individuals were involved in this study who was within 5 years of marriage. The In-Charge Financial Distress/Financial Well-Being (IFDFW) Scale, Financial Management Behavior Scale (FMBS), Kansas Marital Satisfaction Scale (KMSS) and Marital Instability Index (MII) were used for data collection. Data were analyzed using Pearson correlation. The findings showed that there was significant relationship among financial strain, financial management practices, marital satisfaction, marital stability, financial management practices and marital satisfaction. Therefore, it can be concluded that financial does play an important role in satisfaction and stability of marriage.